Integrating English Language Teaching and Environmental Studies Through A Project-Based Digital Storytelling - Pritz Hutabarat; Ririn Syahriani (Universitas Islam Negeri Palopo, 2026)
This mixed-methods case study examined students’ perceptions of an eight-week project-based digital storytelling activity that integrated English language learning with environmental studies. Forty-two undergraduate students at a private university in Indonesia completed a 13-item questionnaire comprising six five-point Likert-scale items and seven open-ended questions; 16 students subsequently participated in semi-structured interviews. Quantitative responses were summarized descriptively, whereas open-ended and interview data were analyzed thematically and integrated during interpretation. Students retrospectively reported a modest increase in environmental awareness, from a mean of 4.05 before the project to 4.29 after it, together with strong engagement (M = 4.19) and motivation to take environmental action (M = 3.93). Most participants regarded digital storytelling as valuable for English learning, particularly for speaking and writing, and described gains in creativity, critical thinking, collaboration, and digital skills. The principal challenges were unequal group participation, scheduling, technical demands, and limited instructional clarity. Students addressed these difficulties through self-directed learning, negotiation, task redistribution, and adaptation. The findings extend project-based learning outcome research by showing how multimodal narrative production can connect affective engagement with local environmental issues to perceived linguistic, collaborative, and digital learning. However, because the awareness ratings were collected retrospectively and the study relied primarily on self-report, the findings indicate perceived change rather than measured causal effects.